Systemic activity and mortality in primary Sjögren syndrome: predicting survival using the EULAR-SS Disease Activity Index (ESSDAI) in 1045 patients. Issue 2 (28th November 2014) - Brito-Zerón, P; Kostov, B; Solans, R; Fraile, G; Suárez-Cuervo, C; Casanovas, A; Rascón, F J; Qanneta, R; Pérez-Alvarez, R; Ripoll, M; Akasbi, M; Pinilla, B; et al.
Abstract : Objective: To score systemic activity at diagnosis and correlate baseline activity with survival in a large cohort of patients with primary Sjögren syndrome (SS). Patients and methods: We include 1045 consecutive patients who fulfilled the 2002 classification criteria for primary SS. The clinical and immunological characteristics and level of activity (EULAR-SS Disease Activity Index (ESSDAI) scores) were assessed at diagnosis as predictors of death using Cox proportional hazards regression analysis adjusted for age at diagnosis. The risk of death was calculated at diagnosis according to four different predictive models. Results: After a mean follow-up of 117 months, 115 (11%) patients died. The adjusted standardised mortality ratio for the total cohort was 4.66 (95% CI 3.85 to 5.60), and survival rates at 5, 10, 20 and 30 years were 96%, 90%, 81% and 60%, respectively. The main baseline factors associated with overall mortality in the multivariate analysis were male gender, cryoglobulins and low C4 levels. Baseline activity in the constitutional, pulmonary and biological domains was associated with a higher risk of death. High activity in at least one ESSDAI domain (HR 2.14), a baseline ESSDAI score ≥14 (HR 1.85) and more than one laboratory predictive marker (lymphopenia, anti-La, monoclonal gammopathy, low C3, low C4 and/or cryoglobulins) (HR 2.82) were associated with overall mortality; these HRs increased threefold to 10-fold when the analysis was restricted to mortality associated with systemic disease. Conclusions: Patients with primary SS, who present at diagnosis with high systemic activity (ESSDAI ≥14) and/or predictive immunological markers (especially those with more than one), are at higher risk of death.